ANALISIS KEMAMPUAN KEUANGAN DAERAH PEMERINTAH KOTA KENDARI - Muslim, Caesar; Dja'wa, Asrianti; Hastuti, Hastuti (Jurnal Multidisipliner Bharasumba, 2023)
Financial capacities be necessary factor and should be seriously attention in regional autonomy context. This research has aim to know the capacity of regional finance of Kendari municipality in the context of supporting the regional autonomy for fiscal years 2009 until 2014. This research was conducted by descriptive method though by some ratios of regional finance, namely: (1) Degree of fiscal autonomy, (2) Efectivity ratio, and (3) Independence ratio. The yield of study, show that regional finance capacity of Kendari government are still very low in category with average degree of fiscal autonomy 7,09%. Government ability to explore and to realize the original income of government also still not effective yet, this is indicate by average efectivity ratio 79%. Also Regional financial auotonomous of Kendari municipality is very low with independence ratio as 11,09% in instructive correlational pattern with central government.